The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4049/jimmunol.179.7.4550
|View full text |Cite
|
Sign up to set email alerts
|

CD83 Expression Is a Sensitive Marker of Activation Required for B Cell and CD4+ T Cell Longevity In Vivo

Abstract: CD83 is a surface marker that differentiates immature and mature human dendritic cell populations. Thymic epithelial cell expression of CD83 is also necessary for efficient CD4+ T cell development in mice. The altered phenotypes of peripheral B and CD4+ T cells, and the reduction of peripheral CD4+ T cells in CD83−/− mice, suggest additional functions for CD83. To assess this, a panel of mAbs was generated to characterize mouse CD83 expression by peripheral leukocytes. As in humans, activation of conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
95
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 52 publications
5
95
0
Order By: Relevance
“…Recent reports have demonstrated that CD83 not only colocalizes with MHCII molecules but also modifies their turnover rate in B cells, T cells, and DCs (10,35). In addition, CD83 is required for the viability of B and CD4 ϩ T cells (10,35). Thus, the high levels of CD83 promoter activity that we observed in both immature and mature B cells may not only prepare these cells for activation but also provide a survival signal.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Recent reports have demonstrated that CD83 not only colocalizes with MHCII molecules but also modifies their turnover rate in B cells, T cells, and DCs (10,35). In addition, CD83 is required for the viability of B and CD4 ϩ T cells (10,35). Thus, the high levels of CD83 promoter activity that we observed in both immature and mature B cells may not only prepare these cells for activation but also provide a survival signal.…”
Section: Discussionmentioning
confidence: 54%
“…Prazma et al (10) have reported the up-regulation of CD83 on CD4 ϩ and CD8 ϩ T cells. Their observation that CD83 upregulation does not occur until 4-6 h after activation can be easily explained by results showing that neither CD83 promoter activity nor preformed intracellular CD83 molecules are present in naïve T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial overexpression of CD83 in CD83 transgenic (CD83tg) mice interfered with the splenic maturation of transitional to follicular B cells and with the peripheral survival of mature naive B cells, whereas CD83 deficiency on the B cells conferred a mild selection advantage in the periphery (28). Naive wild-type B cells rapidly up-regulated CD83 upon activation by BCR or TLR engagement in vitro (6) and in vivo (8,9). The overexpression of CD83 in vivo strongly interfered with the humoral response to thymus-dependent (TD) and thymus-independent (TI) model Ag immunization and to infection.…”
mentioning
confidence: 99%